2006
DOI: 10.17305/bjbms.2006.3125
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Mortality, Recent Trends And Perspectives

Abstract: Considering that a register for cancer was established in Federation of Bosnia and Herzegovina only recently, basic reliable source for the analysis of cancer mortality trends are the data on death cases caused by such diseases. Lack of census as well as standardized mortality rate data makes the study even more difficult to make. The aim of the study is the analysis of the malign diseases trend in the post-war period according to the available data. The study is the descriptive work on the analysis of the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“… 47 However, the meta-analysis dating from the same year 48 reported no significant difference in the risk of death due to cancer between the EVAR and the OSR group. This report draws similar conclusions to our findings, as cancer-related mortality in Slovenia accounts for approximately 30% 49 , 50 , and as a similar rate of cancer-related deaths has also been observed in our study.…”
Section: Discussionsupporting
confidence: 93%
“… 47 However, the meta-analysis dating from the same year 48 reported no significant difference in the risk of death due to cancer between the EVAR and the OSR group. This report draws similar conclusions to our findings, as cancer-related mortality in Slovenia accounts for approximately 30% 49 , 50 , and as a similar rate of cancer-related deaths has also been observed in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Constant rising trend can be seen for the crude death rate of malignant neoplasms of pancreas for period 1999-2011 (figure 13). There is significant difference in crude death rate for period 1999-2006(m=6,48, 95% CI 5,88-7,07) and 2007. In this work we have found that there is no significant difference between men (m=9,35, 95% CI 7,95-10,75) and women (m=7,44, 95% CI 6,20-8,69) in crude death rate for malignant neoplasms of pancreas (figure 14).…”
Section: Global Cancer Facts and Figures 2nd Edition)mentioning
confidence: 91%